THE DETERMINATION OF ECONOMIC EFFICIENCY OF EXPLOITATION OF ARTIFICIAL STRUCTURES - Solomka, V. I. (Science and Transport Progress, 2010)
The basic provisions of determination of economic efficiency of exploitation of artificial structures are considered in the article. There are presented the calculation formulas of expenses on replacement and repair of artificial structures for two variants of exploitation: longevity extension and reliability improvement. The economic effect from making more rational decision on further exploitation of a structure is also determined.